SOCIAL MEDIA SERVICES ARE ONE OF THE REASONS FOR THE INTRUSION OF ENGLISH WORDS INTO THE USE OF THE SERBIAN LANGUAGE AMONG YOUNG PEOPLE (Heritage, 2020)
This work was aimed at studying the influence of English on Serbian through social media services, more precisely Instagram, on the spelling and lexical levels. The analysis was based on a corpus of five user texts detailed in the results. A discussion was also given based on the results obtained. We went with the assumption that the degree of influence of the English language and the hybridization of the Serbian language will be demonstrated under this influence. The results of the analysis at each of the above levels were described and conclusions were made based on the analysis of the results obtained. The greatest influence on the English language was observed at the lexical level in terms of excessive use of anglicisms and the creation of new forms of words under the influence of the English language, but it did not reach even the level of spelling. We also, at the conclusion of this work, suggested some of the measures that can be taken to prevent the intrusion of English words, as well as changes in the Serbian language that are unsubstantiated and unfounded.
Keywords: English, Instagram, influence of English, Serbian.